Financial Behavior, Inclusion, and Technology in MSMEs: The Mediating Impact of Financial Literacy on Performance - Ali Sugih, Frasendi; Fitriyah, Fitriyah (Jurnal Riset Akuntansi dan Keuangan, 2024)
The purpose of this study was to determine the impact of financial behavior, financial inclusion, and financial technology on MSME performance with financial literacy as a mediating variable. The research population included all micro, small, and medium enterprises (MSMEs) located in Ciamis Regency, and the sample was drawn using a random sampling technique. A total of 106 respondents participated; this number was determined by applying Slovin's formula. Information was collected using a questionnaire, which was then processed and analyzed using Partial Least Squares (PLS). The results show that financial behavior has a positive impact on MSME performance, financial inclusion has no significant impact on MSME performance, financial technology has no impact on MSME performance, and financial literacy has a positive impact on MSME performance, financial literacy acts as an intermediary between financial behavior and MSME performance, financial literacy mediates the relationship between financial inclusion and MSME performance, and financial literacy does not mediate the relationship between financial technology and MSME performance. Recommendations for government agencies and financial institutions include providing well-structured financial literacy programs and assisting MSMEs in implementing financial technology. This approach is intended to increase MSMEs' access to financial services as well as their capacity for sustainable growth by equipping them with the knowledge and skills to effectively utilize these resources in their day-to-day business activities.